Cross-neutralizing activity of the chikungunya vaccine VLA1553 against three prevalent chikungunya lineages - Karin Kosulin; Trevor L. Brasel; Jeanon Smith; Maricela Torres; Annegret Bitzer; Katrin Dubischar; Vera Buerger; Robert Mader; Scott C. Weaver; David W.C. Beasley; Romana Hochreiter (Emerging Microbes and Infections)
Cross-neutralization is generally a prerequisite for cross-protection of vaccines against diseases caused by heterologous viruses. Using sera obtained from a randomized clinical phase 3 trial in adults, we investigated the cross-neutralization activity of VLA1553, a vaccine recently approved to prevent chikungunya disease. Analysed in a plaque reduction neutralization test, the three major chikungunya virus (CHIKV) lineages, namely the East Central South African, the West African, and the Asian lineage, were inhibited by CHIKV-specific neutralizing antibodies present in the sera from vaccinated humans. This effect was independent of the time elapsed since vaccination. Moreover, the magnitude of the immune response was similar to the antibody levels detected in sera from convalescent chikungunya patients. Thus, VLA1553 has the potential to diminish the burden of chikungunya disease on a global scale.Trial registration: ClinicalTrials.gov identifier: NCT04546724.